Изделия из стекла из женского погребения IV в. до н.э. из Старшего кургана курганной гряды Три брата - Быковская, Н.В. (Боспорские исследования, 2009)
In 1965, in the outskirts of Kerch an intact female burial dated back to the 4th century BC was found in Starshy kurgan of "Three brothers" ridge. A representative of local nobility was buried in the crypt. She was presumably a priestess of a goddess connected with the fertility of soil. A magnificent set of jewelry, which was found on the buried lady, is stored in the museum of historic valuable (Kyiv). The rest part of the funeral complex is kept in the Kerch Historical and Cultural Reserve. Unique samples of ancient arts - glass medallions with drawings, which might have been used either as amulets or in cult rituals, occupy a significant place among these items from the crypt.